Ethyl acetate extract from Panax ginseng C.A. Meyer and its main constituents inhibit α-melanocyte-stimulating hormone-induced melanogenesis by suppressing oxidative stress in B16 mouse melanoma cells. (17th August 2017) - Jiang, Rui; Xu, Xiao-Hao; Wang, Ke; Yang, Xin-Zhao; Bi, Ying-Fei; Yan, Yao; Liu, Jian-Zeng; Chen, Xue-Nan; Wang, Zhen-Zhong; Guo, Xiao-Li; Zhao, Da-Qing; Sun, Li-Wei
Abstract: Ethnopharmacological relevance: Hyperpigmentation disease involves darkening of the skin color due to melanin overproduction. Panax ginseng C.A. Meyer is a well-known traditional Chinese medicine and has a long history of use as a skin lightener to inhibit melanin formation in China, Korea and some other Asian countries. However, the constituents and the molecular mechanisms by which they affect melanogenesis are not fully clear. Aim of the study: The purpose of this study was to identify the active ingredient in Panax ginseng C.A. Meyer extract that inhibits mushroom tyrosinase activity and to investigate the antioxidative capacity and molecular mechanisms of the effective extract on melanogenesis in B16 mouse melanoma cells. Materials and methods: Aqueous extracts of Panax ginseng C.A. Meyer were successively fractionated with an equal volume of chloroform, ethyl acetate, and n-butyl alcohol to determine the effects by examining the activity of mushroom tyrosinase. The effective fraction was analyzed using HPLC and LC-MS. The antioxidative capacity and the inhibitory effects on melanin content, cell intracellular tyrosinase activity, and melanogenesis protein levels were determined in α-melanocyte-stimulating hormone (α-MSH)-treated B16 mouse melanoma cells. Results: The ethyl acetate extract from Panax ginseng C.A. Meyer (PG-2) had the highest inhibiting effect on mushroom tyrosinase, mainly contained phenolic acids, including protocatechuic acid, vanillic acid, p -coumaric acid, salicylic acid, and caffeic acid, and exhibited apparent antioxidant activity in vitro. PG-2 and its main constituents significantly decreased melanin content, suppressed cellular tyrosinase activity, and reduced expression of tyrosinase protein to inhibit B16 cells melanogenesis induced by α-MSH, and no cytotoxic effects were observed. They also inhibited cellular reactive oxygen species (ROS) generation, increased superoxide dismutase (SOD) activity and glutathione (GSH) level in α-MSH-treated B16 cells effectively. And those activities of its main constituents could reach more than 80% of PG-2. The ROS scavengers N-acetyl-L -cysteine (NAC) had a similar inhibitory effect on melanogenesis. Conclusions: These results suggest that ethyl acetate extract from Panax ginseng C.A. Meyer has the highest effect on inhibiting melanogenesis, and that its main components are polyphenolic compounds, which may inhibit melanogenesis by suppressing oxidative stress. This work provides new insight into the active constituents and molecular mechanisms underlying skin-lightening effect of Panax ginseng C.A. Meyer. Graphical abstract: